Kontribusi Pendapatan Usahatani Jeruk Siam terhadap Pendapatan Rumah Tangga Petani di Desa Tegalsari, Kecamatan Tegalsari, Kabupaten Banyuwangi - PUTRI, RIA FLORA JANUWA; AGUNG, I DEWA GEDE; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018, 2018)
Contribution of Tangerine Farming Revenue in Relation with the Total Household Income of Farmers in the Tegalsari Village, Tegalsari District, Banyuwangi Regency Tangerine, or also known as jeruk keprok in Bahasa, is one of the many species of citrus fruit which has been widely cultivated in various regions in Indonesia. Although its market fluctuate from time to time, but the public interest in tangerine never disappeared.This study aims to determine the contribution of tangerine farming revenue in relation with the total household income of the farmers in the Komojoyo Farmer Group. The results of this research obtained that the average tangerine farming revenue is Rp 35,000,000 per year while the average of non-farming revenue is amounted to Rp. 8,761,304 per year. It proved that citrus farm revenue is greater than non-farm revenue. There are constraints faced by Komojoyo Farmer Group, namely, the aphid pest, the lack of guidance from agricultural counselor, and sales methods are still using the services of middlemen. It can be evidenced from the percentages obtained: the pest was 11%, guidance from agricultural counselor at 65%, and sales of middlemen by 24%. From these percentages, it can be seen that the biggest obstacle faced by Komojoyo farmer group is the lack of guidance from agricultural counselor.